1991
DOI: 10.1897/1552-8618(1991)10[517:ttoewm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Tests of Effluents With Marsh Plants in Water and Sediment

Abstract: Methods are described for toxicity testing of water and sediment with two varieties of the freshwater marsh plant Echinochloa crusgalli (Linneaus) Palisot de Beauvois (Poaceae), and complex effluents. Two tests are described: a seed germination and early seedling growth test in water, and a survival and seedling growth test in natural and synthetic sediments. Effects of effluents from a sewage treatment plant, tannery, textile mill, pulp and paper mill, coking plant and sewage treatment plant included inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In addition, it has been used to assess and monitor the toxicity of PCB, HCH, herbicides and PAHs in contaminated soil (Walsh et al 1991;Meier et al 1997;Maila and Cloete 2002;Bidlan et al 2004). We found that reductions in seed germination rates were not prominent (Figs.…”
Section: -Day Seed Germination/root Elongation Testsmentioning
confidence: 92%
“…In addition, it has been used to assess and monitor the toxicity of PCB, HCH, herbicides and PAHs in contaminated soil (Walsh et al 1991;Meier et al 1997;Maila and Cloete 2002;Bidlan et al 2004). We found that reductions in seed germination rates were not prominent (Figs.…”
Section: -Day Seed Germination/root Elongation Testsmentioning
confidence: 92%
“…Walsh et al (1991) use marsh plants to develop tests for toxicity data from textile effl uents as a standard for regulating permissible discharges. Walsh et al (1991) use marsh plants to develop tests for toxicity data from textile effl uents as a standard for regulating permissible discharges.…”
Section: Waste Water Treatmentmentioning
confidence: 99%
“…Formulated sediment was prepared using methods similar to those of previous investigators [6,[20][21][22]. White silica #1 (New England Silica, Windsor, CT, USA), with a median grain size of 300 m, was used for sand.…”
Section: Formulated Sedimentmentioning
confidence: 99%